Vaccination with novel low-molecular weight proteins secreted from Trichinella spiralis inhibits establishment of infection - Mellina T. Srey; Alessia Taccogna; Yelena Oksov; Sara Lustigman; Pei-Yi Tai; John Acord; Murray E. Selkirk; Tracey J. Lamb; David B. Guiliano; David Joseph Diemert (Public Library of Science (PLoS), 2020)
Trichinella spiralis muscle stage larvae (mL1) produce excretory-secreted products (ESPs), a complex mixture of protein, which are believed to be important for establishing or maintaining an infection niche within skeletal muscle and the intestine. Studies of both whole ESPs and individual cloned proteins have shown that some ESPs are potent immunogens capable of eliciting protective immune responses. Here we describe two novel proteins, Secreted from Muscle stage Larvae SML-4 and SML-5 which are 15 kDa and 12 kDa respectively. The genes encoding these proteins are highly conserved within the Trichinellids, are constituents of mL1 ESP and localized in the parasite stichosome. While SML-5 is only expressed in mL1 and early stages of adult nematode development, SML-4 is a tyvosylated glycoprotein also produced by adult nematodes, indicating it may have a function in the enteral phase of the infection. Vaccination with these proteins resulted in an impaired establishment of adult stages and consequently a reduction in the burden of mL1 in BALB/c mice. This suggests that both proteins may be important for establishment of parasite infection of the intestine and are prophylactic vaccine candidates. Author summary Author summary Trichinellosis, also known as trichinosis, is a disease caused by consuming raw or undercooked meat from animals infected with muscle stage larvae of Trichinella spiralis. These worms cause infection when L1 (newborn) larvae migrate and invade skeletal muscle remodeling muscle cells into long-lived nurse cells which serve as reservoirs for the parasite. The establishment of nurse cells allows T. spiralis to better survive within the host because factors, such as blood vessel formation, bring required components for survival to the worms. We previously found three novel proteins termed Secreted from Muscle stage Larvae (SML)-1, -2, and -3 by transcriptomic analysis. In this study, we further expand our previous findings by identifying two novel low molecular weight proteins SML-4 and SML-5, which can elicit protective responses against challenge infections with T. spiralis.